CSR SAMPAI “I’M LOVIN’ IT”: MEMBANGUN KEPUASAN PELANGGAN MELALUI CITRA MEREK AFEKTIF DI INDUSTRI FAST FOOD - Tania Monica Potu; Yanuar Dananjaya; Hananiel Mennoverdi Gunawan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
The purpose of this study is to investigate how brand image mediates the relationship between CSR and customer satisfaction, with a focus on the emotive dimension. Economic, social, and environmental dimensions make up the multifaceted idea of Corporate Social Responsibility (CSR). This study uses a survey method and a quantitative approach, focusing on consumers who have purchased products from McDonald’s and are aware of its CSR initiatives. Structured questionnaires will be used to gather data, and the Statistical Package for Social Sciences (SPSS) will be used for analysis. The suggested correlations between the variables will be investigated using multiple regression analysis and mediation testing. The purpose of this study is to determine if CSR has a substantial impact on customer satisfaction and affective brand image, as well as to evaluate the mediating function of affective brand image in this connection. Additionally, it looks at how emotional brand impressions are impacted by the economic, social, and environmental CSR components. This study is new since it only examines the emotive aspect of brand image as a mediating variable, leaving out the functional aspect, which has been extensively studied in earlier research. Furthermore, a better understanding of how CSR activities affect consumer satisfaction and emotional brand perceptions in the fast-food business may be gained by applying a three-level CSR framework: economic, social, and environmental.